Sand and Silty-sand Soil Stabilization Using Bacterial Enzyme Induced Carbonate Precipitation (BEICP) - Hoang Phuong Tung
Chapter 1. Introduction; Chapter 2. Literature review; Chapter 3. Sand and silty-sand soil stabilization using bacterial enzyme induced carbonate precipitation (BEICP); ...